Genetic associations of the interleukin locus at 1q32.1 with clinical outcomes of cutaneous melanoma. Issue 4 (20th January 2015) - Rendleman, Justin; Vogelsang, Matjaz; Bapodra, Anuj; Adaniel, Christina; Silva, Ines; Moogk, Duane; Martinez, Carlos N; Fleming, Nathaniel; Shields, Jerry; Shapiro, Richard; Berman, Russell; Pavlick, Anna; et al.
Abstract : Background: Due to high melanoma immunogenicity, germline genetic variants in immune pathways have been studied for association with melanoma prognosis. However, limited candidate selection, inadequate power, or lack of independent validation have hampered the reproducibility of these prior findings, preventing personalised clinical applicability in melanoma prognostication. Our objective was to assess the prognostic utility of genetic variants in immunomodulatory pathways for prediction of melanoma clinical outcomes. Methods: We genotyped 72 tag single nucleotide polymorphisms (SNPs) in 44 immunomodulatory genes in a population sample of 1022 melanoma patients and performed Cox regression analysis to test the association between SNPs and melanoma recurrence-free (RFS) and overall survival (OS). We have further investigated the most significant associations using a fine mapping strategy and followed with functional analyses in CD4+ T cells in a subset of 75 melanoma patients. Results: The most significant associations were found with melanoma OS for rs3024493 in IL10 at chromosome 1q32.1 (heterozygous HR 0.58, 95% CI 0.39 to 0.86; p=0.0006), a variant previously shown to be linked with autoimmune conditions. Multiple additional SNPs at 1q32.1 were also nominally associated with OS confirming at least two independent association signals in this locus. In addition, we found rs3024493 associated with the downregulation of interleukin 10 (IL10) secretion in CD4+ T cells. Conclusions: We discovered novel associations of IL10 with melanoma survival at 1q32.1, suggesting this locus should be considered as a novel melanoma prognostic biomarker with potential for aiding melanoma patient management. Our findings also provide further support for an alternative role of IL10 in stimulation of anti-tumour immune response.